Am I being watched? The role of researcher presence on toddlers' behaviour during 'everyday' pain experiences: a pilot study. Issue 9 (1st September 2020) - O'Sullivan, Grace; McGuire, Brian; Roche, Michelle; Caes, Line
Abstract: Objective: Paediatric research on 'everyday' pain experiences is sparse, stemming from a lack of appropriate methodologies. We explored the feasibility of two methodologies for conducting naturalistic observations of 'everyday' pains within family's homes, against an established methodology for day-care observations. Design: Within family homes, video-cameras recorded a typical morning or afternoon (maximum three hours), either with, or without researcher presence. To compare feasibility, children in day-care were observed by researchers for three hours without video-recording. Outcome measures: logistics of observation, child pain behaviours, caregiver responses to child pain. Results: Thirteen children ( M age = 45.4 months) were recorded at home, experiencing 14 pain events. Researcher presence increased child distress intensity, but reduced the number of pain events compared to sessions without a researcher. Thirty-two children ( M age = 48.4 months) were observed in day-care, experiencing 44 pain events. Children experiencing pain events in day-care exhibited decreased distress and lower personal control than those observed at home. Across all conditions, caregivers engaged mostly in physical comfort. Researcher estimates of child pain were highest if scored while present in the home. Conclusions: Observing everyday pain events within the child's natural environment is feasible and may provide insight into the social context of childhood pain experiences.